2013
DOI: 10.1088/0953-2048/26/7/075011
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis from separate oxide targets of high quality La2−xSrxCuO4thin films and dependence with doping of their superconducting transition width

Abstract: A series of superconducting La 2−x Sr x CuO 4 thin films, with 0.09 x 0.22, is grown over (100)SrTiO 3 substrates by means of a novel pulsed laser deposition method devised to increase the homogeneity and control of doping. We employ two separate parent oxide targets that receive ablation shots at arbitrary computer-controlled relative rates, instead of the conventional procedure that uses a single target whose doping determines the one of the film. We characterize the films both through conventional technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…Also, for our R(T) calculations we shall use two alternative calculations, so as to be confident about the validity of the results: Finite-element computations first, and then effective-medium formulae (both paths have been successful in other studies of structured HTS [30][31][32][33][34][35], and we shall also include some confirming example comparisons with real data). Let us provide the details of all such procedures in the following sections.…”
Section: Methods For Structured Nonpatterned Resistive Hts Tesmentioning
confidence: 99%
See 3 more Smart Citations
“…Also, for our R(T) calculations we shall use two alternative calculations, so as to be confident about the validity of the results: Finite-element computations first, and then effective-medium formulae (both paths have been successful in other studies of structured HTS [30][31][32][33][34][35], and we shall also include some confirming example comparisons with real data). Let us provide the details of all such procedures in the following sections.…”
Section: Methods For Structured Nonpatterned Resistive Hts Tesmentioning
confidence: 99%
“…The critical fluctuations around the transition play an important role in HTS and have been studied in detail, e.g., in [32,[41][42][43][44][45][46][47][48]. The effects of critical fluctuations in the resistance curves are commonly summarized via the so-called paraconductivity, ∆σ, defined as the additional contribution to the electrical conductivity due to fluctuations: In particular, the total conductivity σ(T) near the transition becomes…”
Section: Rounding Of R(t) Near the Superconducting Transition Due To Critical Phenomenamentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the penetration depth measurements in bulk YBa 2 Cu 3 O 7−x found no signatures Dragana Popović dragana@magnet.fsu.edu 1 National High Magnetic Field Laboratory, Florida State University, 1800 E. Paul Dirac Drive, Tallahassee, FL 32310, USA of the BKT physics in thick films [6] or crystals [7], while dc transport measurements suggested BKT-like behavior in bulk samples of several cuprates (see, e.g., Refs. [8][9][10][11]). A recent study of the paraconductivity and the I -V characteristics in highly underdoped La 2−x Sr x CuO 4 (x = 0.07 and 0.08) thick films (150 CuO 2 layers) in zero magnetic field [5] showed that the effective dimensionality of the samples is 2D and that the thermally-driven transition to the superconducting state is of the BKT type with a large vortex-core energy μ ≈ 1.4μ XY (μ XY = π 2 J s /2 is the conventional value that it assumes in the XY model; J s is the superfluid stiffness).…”
Section: Introductionmentioning
confidence: 99%